ATR-FTIR pre-screening analyses for determining radiocarbon datable bone samples from the Kings' Valley, Egypt. (March 2022) - Quiles, Anita; Lebon, Matthieu; Bellot-Gurlet, Ludovic; Bickel, Susanne
Abstract: The tomb KV 40 in the Kings' Valley (Luxor, Egypt) has revealed mummified and highly fragmented remains of 83 adults, children, new-borns and infants, some of whom were, according to inscriptions, 18th dynasty king's sons or daughters (∼1370 BCE). This tomb was then secondarily reused by priestly families during the 22nd to early 25th dynasty (∼900-700 BCE). Radiocarbon dating of such bone remains would allow the evaluation of the ratio of burials by period and the identification of those from the 18th dynasty. As the bones were buried within a shaft tomb under hot and dry climatic conditions and have been partially burnt by fires, the applicability of radiocarbon dating on collagen extracted from them was uncertain and highly challenging. Prior to collecting samples, the state of collagen preservation in the bones had to be evaluated to ensure the feasibility of radiocarbon dating. Following the method of Lebon et al. (2016), three ATR-FTIR systems (benchtop and portables) were used to determine the effective and appropriate calibration of each instrument thanks to a set of reference bones. From this, we provide methodological recommendations to ensure the reliability of the quantifications obtained whatever the instrument used. As a demonstration of the efficiency of the proposed methodology, portable ATR-FTIR spectroscopy has been tested in situ in KV 40, and the N %wt contents thus evaluated have been compared to ATR-FTIR analyses in a laboratory (using a different spectrometer) and to elemental analyses. The results obtained on thirteen KV 40 individuals clearly show quite good consistency on ATR-FTIR analyses between both spectrometers, validating the relevance of this on-site analytical approach with each spectrometer properly calibrated and measurements performed according to a strict protocol. Regarding the estimation of the nitrogen content, all the KV 40 samples are radiocarbon datable despite challenging preservation conditions. Discrepancies have been highlighted between some of the ATR-FTIR results and elemental analyses, the latter systematically providing higher N %wt than the former. For these samples, the C %wt contents are also very high, showing that these bones are contaminated by organic materials. This underlines the efficacy of the ATR-FTIR analysis specifically for the quantification of bone collagen. The developed analytical approach based on the ATR-FTIR method and its mobile instrumentation clearly operates effectively on site and under challenging conditions, which opens up new perspectives for the collection of bone remains prior to radiocarbon dating. Highlights: Issues linked with radiocarbon dating application on human bones from the tomb KV 40. On-site quantification of bone collagen from Egyptian mummies by ATR-FTIR. ATR-FTIR prescreening method enabling in situ identification of 14 C datable bones. Validation of the methodology on three ATR-FTIR systems (bench-top and portable).